1988
DOI: 10.1139/z88-058
|View full text |Cite
|
Sign up to set email alerts
|

A study of Gyrodactylus colemanensis Mizelle and Kritsky, 1967 and Gyrodactylus salmonis (Yin and Sproston, 1948) (Monogenea) parasitizing captive salmonids in Nova Scotia

Abstract: Gyrodactylus colemanensis Mizelle and Kritsky, 1967 and Gyrodactylus salmonis (Yin and Sproston, 1948) parasitized Salvelinus fontinalis, Salmo gairdneri, and Salmo salar at a fish farm in Nova Scotia. Gyrodactylus colemanensis occurs on the edges of fins and clings delicately to the skin surface. Gyrodactylus salmonis embeds its marginal hooks deeply into the epidermis and occurs all over the body surface except on the fin edges. The parasites gain entrance to the hatchery on infected stocks arriving from oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…were not associated with any gross pathology. Similarly, Cusack (1986) reported that G. colemanensis did not influence the growth or survival of the fry of rainbow trout, Oncorhynchus mykiss and Cone and Cusack (1988) found no evidence of lesions in infections of G. colemanensis and G. salmonis on salmonids. Whether or not the histopathological effects produced by M. clarii influence the growth, survival and/or mortality of C. gariepinus still need to be studied experimentally.…”
Section: Discussionmentioning
confidence: 93%
“…were not associated with any gross pathology. Similarly, Cusack (1986) reported that G. colemanensis did not influence the growth or survival of the fry of rainbow trout, Oncorhynchus mykiss and Cone and Cusack (1988) found no evidence of lesions in infections of G. colemanensis and G. salmonis on salmonids. Whether or not the histopathological effects produced by M. clarii influence the growth, survival and/or mortality of C. gariepinus still need to be studied experimentally.…”
Section: Discussionmentioning
confidence: 93%
“…This seems also to be valid to G. salmonis. In laboratory experiments (CONE et ODENSE, 1984;CUSACK, 1986;CUSACK et CONE, 1986;CONE et CUSACK, 1988), however, G. salmonis was pathogenic to the expérimental host, Salvelinus fontinalis, while infestations by G. co/emanens/s caused no clinical sign. This may imply that G. salmonis (G. sa/an's-group) is a true salmonid parasite, while G. colemanensis (G. arcuatus-group) is not spécifie to salmonids.…”
Section: Fish Farmingmentioning
confidence: 90%
“…Hitherto, however, the species is not found on a spécifie host in natural waters. Furthermore, on salmonids in farms the species seems not to cause disease (CUSACK, 1986;CONE et CUSACK, 1988). Thus the species in fish farms may use salmonids as temporary hosts.…”
Section: Distribution Of Species Groups Of Gyrodactylus On Salmonidsmentioning
confidence: 99%
See 2 more Smart Citations